Multiple Positive Solutions for a System of Nonlinear Caputo-Type Fractional Differential Equations - Hongyu Li; Yang Chen (Journal of Function Spaces)
By using fixed-point index theory, we consider the existence of multiple positive solutions for a system of nonlinear Caputo-type fractional differential equations with the Riemann-Stieltjes boundary conditions.